2021
DOI: 10.1371/journal.pone.0248182
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genomes of Impatiens cyanantha and Impatiens monticola: Insights into genome structures, mutational hotspots, comparative and phylogenetic analysis with its congeneric species

Abstract: Impatiens L., the largest genus in the family Balsaminaceae with approximately 1000 species, is a controversial and complex genus that includes many economically important species well known for medicinal and ornamental values. However, there is limited knowledge of molecular phylogeny and chloroplast genomics, and uncertainties still exist at a taxonomic level. In this study, we have assembled four chloroplast genomics specimens of Impatiens cyanantha and Impatiens monticola, which are found at the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Occasional short sequence repeats and mutations in DNA sequences can be extended into longer tandem repeats through slip-chain mismatch events, and transposon-mediated insertion and copy slip may be responsible for both direct and reverse dispersed repeats (Levinson and Gutman, 1987). In this paper, the forward and palindromic repeats were the most common repeat types and most of the dispersed repeats were less than 40 bp, as the previous studies was reported (Liu et al, 2019;Kirov et al, 2020;Luo et al, 2021).…”
Section: Discussionmentioning
confidence: 50%
“…Occasional short sequence repeats and mutations in DNA sequences can be extended into longer tandem repeats through slip-chain mismatch events, and transposon-mediated insertion and copy slip may be responsible for both direct and reverse dispersed repeats (Levinson and Gutman, 1987). In this paper, the forward and palindromic repeats were the most common repeat types and most of the dispersed repeats were less than 40 bp, as the previous studies was reported (Liu et al, 2019;Kirov et al, 2020;Luo et al, 2021).…”
Section: Discussionmentioning
confidence: 50%
“…The reference I. tectorum genome (153,253 bp) was the third in size. The coding regions had less divergence than the noncoding sequence regions owing to the variable regions [92][93][94]. The IR regions were more conserved, whereas the LSC and SSC regions were more divergent.…”
Section: Identification Of Highly Variablementioning
confidence: 99%
“…The chloroplast genome (CpDNA) and nuclear genome were currently widely used in plant genetic diversity, phylogenetic relationships, and lineage geography. Luo et al (2021a, b) sequenced the chloroplast genome of some Impatiens and identi ed some long repeat sequences and simple repeats, which provided valuable and important genomes for Impatiens species identi cation and phylogenetic evolution. Our research aimed to systematically investigate Impatiens in eastern Yunnan, and provide basic data for the protection of Impatiens resources and species diversity in this area.…”
Section: Introductionmentioning
confidence: 99%